2015
DOI: 10.1007/s00580-015-2207-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value and clinical significance of TCR rearrangements for MRD monitoring in ALL patients

Abstract: Acute lymphoblastic leukemia is a hematological malignancy of lymphoid progenitor cells associated with excessive proliferation of lymphocytes, and lymphocyte markers can be used for the diagnosis and assessment of disease. Cell surface receptors, including T cell receptor and immunoglobulin (on T and B cells, respectively), are among the most important lymphocyte markers. Gene segment variation, i.e., involvement of several genes in the expression of each receptor, is effective on extensive rearrangement of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Correspondingly, previous studies have shown that the results of TCR gene rearrangements could be prognosis markers in acute lymphoblastic leukemia (ALL). 36 Not only that, we observed a specific module of V-J genes using WGCNA method, 26 the relationship between highly correlated V-J genes in the module and clinical features were investigated ( Figure 3 ). As far as we know, this is the first study to identify the module of V-J genes usage contributing to the TCR repertoires associated with clinical pathogenic characteristics.…”
Section: Discussionmentioning
confidence: 93%
“…Correspondingly, previous studies have shown that the results of TCR gene rearrangements could be prognosis markers in acute lymphoblastic leukemia (ALL). 36 Not only that, we observed a specific module of V-J genes using WGCNA method, 26 the relationship between highly correlated V-J genes in the module and clinical features were investigated ( Figure 3 ). As far as we know, this is the first study to identify the module of V-J genes usage contributing to the TCR repertoires associated with clinical pathogenic characteristics.…”
Section: Discussionmentioning
confidence: 93%
“…The development of PCR-based approaches in the last years has facilitated the complex characterization and classification of malignant diseases, patient stratification and monitoring of minimal residual disease (MRD) [9]. Following flow-cytometric analysis of T or B-cell populations, PCR-based clonality assays are requested to identify whether the populations of cells are derived from clonal or polyclonal expansions [10,11].…”
mentioning
confidence: 99%